A walk‐in clinic as an alternative approach to reaching non‐attenders of the cervical cancer screening program in the North Denmark region—a pilot study - Rikke Ekkelund Bonefeld; Anna Poulsgaard Frandsen; Jette Christensen; Thomas Larsen; Henriette Strøm Kahr (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Up to 39% of women in Denmark do not participate regularly in the cervical cancer screening program and initiatives to increase participation are called upon. The primary aim of this study was to describe previous screening history and characteristics of women attending screening in a walk‐in clinic. Furthermore, we wanted to investigate barriers to cervical cancer screening. Material and methods We designed a walk‐in clinic that was open 2 days a week from 16.00 to 19.00 h, located in the Departments of Gynecology in the two main hospitals of the North Denmark Region. The main purpose of the clinic was cervical cancer screening and the study period was 5 months. Women who were not eligible for screening or had other health complaints were referred to their general practitioner. The women included in the study, filled out a questionnaire regarding educational and occupational status; their screening history was registered using data from the Danish Pathology Register. Results During the study period, 255 women visited the walk‐in clinic. The final study population consisted of 249 women who met the inclusion criteria. Age range of participants was 23–77 years, with a median age of 45 years. The majority of the participants were currently employed (81%) or students (10%), the remaining being retired (5%) or unemployed (4%). Screening history showed that 138 (55.4%) of the women were on time for the screening or delayed less than 6 months compared to their recommended screening interval. Sixty‐one women (24.5%) were delayed >6 months but <2 years. Fifty women (20.1%) were classified as non‐attenders, with more than a 2‐year delay in their screening. In the group of non‐attenders, eight women had never been screened. Of the remaining 42 women, the median time since last screening was 8.2 years (range 5.0–25.3 years). Conclusions Women attending the walk‐in clinic tended to be primarily actively working or students (91%). All age groups in the screening population were represented. Screening history showed that 44.6% had not followed the recommended screening program.